Motor Rhythm Dissection From the Backward Circuit in C. elegans - Yu, Bin; Wang, Ya; Gao, Shangbang (Frontiers in Molecular Neuroscience, 2022)
Motor rhythm is initiated and sustained by oscillatory neuronal activity. We recently discovered that the A-class excitatory motor neurons (MNs) function as intrinsic oscillators. They drive backward locomotion by generating rhythmic post-synaptic currents (rPSCs) in body wall muscles. The molecular underpinning of the rPSCs however is not fully elucidated. We report here that rPSCs exhibits three patterns, namely the phasic-, tonic- and long lasting-types, each with distinct kinetics and channel-dependence. While the phasic rPSCs activation relies more on the Na+ leak channel (NCA), the tonic rPSCs are primarily dependent on the P/Q/N-type voltage-gated Ca2+ channels (VGCC) UNC-2 and L-type VGCC EGL-19. Three K+ channels, the BK-type Ca2+-activated K+ channel SLO-1, Na+-activated K+ channel SLO-2 and voltage-gated K+ channel (Kv4) SHL-1, exhibit differential inhibition of rPSCs. The elaborate regulation of rPSCs by different channels, through increasing or decreasing the rPSCs frequency and/or charge, substantially affected the reversal velocity. The molecular dissection of different A-MNs-rPSCs components, therefore, revealed the multiplex motor rhythm mechanisms.